A Decomposition Model for Risk Equity and Network Accessibility Trade off in Hazardous Material Transportation: An Empirical Study - Mahmoudabadi, Abbas (Transportation Development Research, 2025)
A major part of goods and substances transported across the world is categorized as hazardous materials (Hazmat) or dangerous goods. Hazmat transportation has potential risks in nature, so it is essential to avoid risk agglomeration in the most frequently selected routes while transport planning in practice. The concern leads authorities and practitioners to prevent risk concentration, so-called risk equity or risk distribution, but it affects a crucial parameter in transport planning known as network accessibility. This study proposes a procedure and develops the corresponding mathematical models for trading off between risk equity and network accessibility. The linearization technique of decomposition transforms the nonlinear format of equations into the linear ones as well as the risk distribution technique of Min(Max) spreads Hazmat transport risk over the network. The inter-relation between risk equity and accessibility has been illustrated to be easily understood and typically studied as a case study in an intercity road network. The proposed procedure has been performed using experimental data, including network specifications and the Origin-Destination matrix of Hazmat planned to be transported. Based on the research results, applying Hazmat risk distribution techniques and network accessibility measures have a reverse relationship. Therefore, authorities should be aware of the effects of risk equity and road network accessibility in Hazmat transport planning.